2011
DOI: 10.1007/s10126-011-9411-6
|View full text |Cite
|
Sign up to set email alerts
|

Cold-adapted Features of Arginine Kinase from the Deep-sea Clam Calyptogena kaikoi

Abstract: The heterodont clam Calyptogena kaikoi, which inhabits depths exceeding 3,500 m where low ambient temperatures prevail, has an unusual two-domain arginine kinase (AK) with molecular mass of 80 kDa, twice that of typical AKs. The purpose of this work is to investigate the nature of the adaptations of this AK for functioning at low temperatures. Recombinant C. kaikoi AK constructs were expressed, and their two-substrate kinetic constants (k(cat), K(a), and K(ia)) were determined at 10°C and 25°C, respectively. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 61 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Hyperthermophilic bacteria isolated from marine sediments and seawater can utilize glucans as well as hemicellulose such as xylans and mannans [1]. Cold-adapted amylase and arginine kinase were produced by marine bacteria [23,30].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermophilic bacteria isolated from marine sediments and seawater can utilize glucans as well as hemicellulose such as xylans and mannans [1]. Cold-adapted amylase and arginine kinase were produced by marine bacteria [23,30].…”
Section: Introductionmentioning
confidence: 99%
“…It facilitates the reversible exchange of the gamma-phosphoryl group between ATP and arginine, resulting in the production of ADP, phosphorylated guanidine, and energy (Uda et al, 2006). Researchers found that the catalytic efficiency of arginine kinases with two domains, derived from cold seep clams, exhibited a threefold increase at a temperature of 10 °when compared with that at to 25 ° (Suzuki et al, 2012). This finding suggests a potential mechanism by which cold seep shellfish can adapt to low-temperature surroundings.…”
Section: Cold Adaptation-arginine Kinasementioning
confidence: 99%